متطلبات أبعاد الإدارة الاستراتيجية للموارد البشرية- مقاربة تحليلية لنموذج المطابقة ونموذج هارفارد - بن عطا الله, بلقاسم (جامعة الوادي - University of Eloued, 2023)
This research paper seeks To provide a theoretical framework Contributes to the identification of the basic concepts of strategic human resource management and highlighting its dimensions and foundations, by presenting the foundations of building a strategic human resource management, then addressing the concept, characteristics and dimensions of strategic human resources management, This study also touched on the two most important models that dealt with the strategic human resource management, namely the matching model, and the Harvard model, by presenting the most important principles and characteristics that distinguish them and presenting a comparison between them.
The requirements of the dimensions of Strategic Human Resources Management- An analytical approach to the Matching Model and the Harvard Model
مقال
Keywords: إدارة استراتيجية للموارد البشرية ; نموذج المطابقة ; نموذج جامعة هارفارد